2001
DOI: 10.1088/0964-1726/10/3/314
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-based damage detection in civil engineering: excitation sources and temperature effects

Abstract: This paper discusses two very relevant practical issues in the application of vibration-based health monitoring to civil engineering structures: the excitation source and the effect of temperature. The idea of vibration-based damage detection is to measure dynamic characteristics such as eigenfrequencies, damping ratios and mode shapes on a regular basis. The state, and eventually degradation, of the structure is reflected in the evolution of these characteristics. Unfortunately, it is not only the health of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
199
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(207 citation statements)
references
References 8 publications
5
199
0
3
Order By: Relevance
“…The dominant environmental factor affecting the dynamic response of bridge structures is generally considered to be temperature. Previous studies [3][4][5] have found fluctuations in modal frequency to be correlated with ambient temperature, although different mechanisms have been used to explain this. Cornwell et al [4] suggested that the thermal gradient across the deck of the Alamosa canyon bridge drove the measured fluctuations in frequency.…”
Section: Results From Tamar Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant environmental factor affecting the dynamic response of bridge structures is generally considered to be temperature. Previous studies [3][4][5] have found fluctuations in modal frequency to be correlated with ambient temperature, although different mechanisms have been used to explain this. Cornwell et al [4] suggested that the thermal gradient across the deck of the Alamosa canyon bridge drove the measured fluctuations in frequency.…”
Section: Results From Tamar Analysismentioning
confidence: 99%
“…Cornwell et al [4] suggested that the thermal gradient across the deck of the Alamosa canyon bridge drove the measured fluctuations in frequency. In colder climates significant shifts in frequency between above and below freezing temperatures have been attributed to an increase in stiffness explained by the Young's modulus of the asphalt on the deck at colder temperatures [5].…”
Section: Results From Tamar Analysismentioning
confidence: 99%
“…By following the dynamic behavior of the structure in real time, it is possible to apply statistical methods in order to detect small damages and remove the effects of the environment ( [3], [4], [5] and [6]). This opens the way to the development of automated damage detection systems and could allow going from an "on schedule" maintenance to an "on demand" maintenance, therefore greatly reducing the costs and the risks of failure between two maintenances.…”
Section: Introductionmentioning
confidence: 99%
“…(35) are stored and introduced in Eq. (42) to obtain the augmented state space model. In the following, the KF algorithm based on this approach will be indicated as 'H-fractional KF' and the corresponding noise is denoted as 'H-fractional noise', respectively.…”
Section: Exponentially Correlated Wind Gustsmentioning
confidence: 99%
“…The first use of the ambient vibration technique for the dynamic characterization of full-scale structures is reported in the seventies. Since then the technique is extensively used in engineering in the scope of parameter identification (frequencies, damping ratios and modal shapes) [27,41,40,17,6,44,22], model updating [26,22] as well as damage detection and health monitoring [20,42,33] of slender structures such as pedestrian bridges, chimneys, long-span frame structures or high-rise buildings.…”
Section: Introductionmentioning
confidence: 99%